Secchi disk, ichthyometer, bowl and net-tank as social technologies in fish farming (Research, Society and Development, 2021)
The objective of this study was to develop social technologies for family fish farming, which cultivate tambaqui (Colossoma macropomum). The technologies were built during the course of Good Management Practices in the municipality of Curralinho, Marajó archipelago (Pará - Brazil), in March 2020. At the end of the course, a workshop was held to produce the management equipment, among students, teachers and local fish farmers. The project trained men and women from different rural communities. Secchi's disk, ichthyometer, bowl and net-tank were the technologies built and tested in local fish farms. In conclusion, the extension activities and the construction of low cost equipment for family fish farming were successful. The social technologies built, proved to be technically viable, being a sustainable alternative for the production and management of local tambaqui.